The social construction of identity in the Golestan quarter of Sabzevar: Narrative research of challenges and identity of the Ghorbat community. Issue 1 (June 2019) - Ghodrati, Hossein; Gharbi, Mosareza
Abstract : This study is an invitation to concentrate on the social and cultural dimensions of Golestan quarter for an understanding of the situation, and to take advantage of that to organize and solve the problems of the neighbourhood in the urban fabric of Sabzevar. This is a narrative research conducted with the participation of six inhabitants of the Golestan quarter in Sabzevar. The results show that given the gap which exists between the inhabitants of Golestan quarter and other people in the city, the concept of social identity is one of the most important components which should be investigated in order to understand the Golestan people. In this regard, from the past to the present, identification procedures of Golestan inhabitants can be classified in terms of pre-modern and modern processes. Today, Golestanis are in transition mode towards obtaining a modern identity. Understanding the nature, objectives, and strategies of these processes seem necessary for any planning for this neighbourhood.